RISK ANALYSIS DURING THE BRIDGE CONSTRUCTION AND OPERATION IN BELARUS REPUBLIC - Hulytska, O. V.; Kushch, N. N.; Shymanska, O. S. (Science and Transport Progress, 2010)
In the paper the industrial risk analysis during the bridge construction and operation is presented as well as the recommendations for the risk minimization are proposed.